A Study of the Historical Perspective on ISIS Impact: Unveiling Extremism in Malaysia - Nur Adillah Omar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The radical and extremist ideologies propagated by the ISIS group have left a profound impact not only on the international phenomenon but also regionally. This is exemplified by the bombing at Movida Club in Puchong in 2016, resulting in casualties among Malaysians. In addressing this critical issue, the study aims to delve into the history of the emergence of ISIS group in Malaysia. This study will utilize qualitative methods, specifically library research through content analysis to analyse and gather data from diverse sources such as books, articles, journals, magazines, and newspapers. The primary objective is to understand the historical context of ISIS group in Malaysia in order to mitigate the proliferation of radicalism and extremism ideologies in Malaysia. The result of this study demonstrates ISIS group have emergence in Malaysia through the Islamic Revivalism (1970), Jemaah Islamiyyah (JI) In Malaysia by Nasir Abbas and Yazid Sufaat (1993 – 2015) and the returnees of the Afghan Alumni, Kumpulan Mujahideen Malaysia (KMM) in Malaysia whom is Zainon Ismail, Nasir Abbas and Yazid Sufaat. In brief, this study is expected to provide valuable insights for policymakers, law enforcement agencies, and researchers working in the field of counterterrorism and extremism after understood the pattern of the ISIS group in terms of recruitment, planned attacks in order to predict the next pattern of recruitment and attacks.